Transferable chloramphenicol resistance determinant in luminous Vibrio harveyi from penaeid shrimp Penaeus monodon larvae - Abraham, Thangapalam Jawahar (Journal of Fisheries, 2016)
Antibiotic-resistant luminous Vibrio harveyi strains isolated from Penaeus monodon larvae were screened for the possession of transferable resistance determinants. All the strains were resistant to chloramphenicol and the determinant coding for chloramphenicol resistance was transferred to Escherichia coli at frequencies of 9.50x10-4 to 4.20x10-4. The results probably suggest the excessive use of chloramphenicol in shrimp hatcheries to combat luminous vibriosis.